Integration of hydrogenation and dehydrogenation system for hydrogen storage and electricity generation – simulation study. (26th July 2019) - Hamayun, Muhammad Haris; Hussain, Murid; Maafa, Ibrahim M.; Aslam, Rabya
Abstract: The present study combines methylcyclohexane dehydrogenation and toluene hydrogenation systems to produce steam for power generation. Methylcyclohexane dehydrogenation requires heat input, which has been accomplished using heat, released from toluene hydrogenation system, and heat exchange with steam, produced from the steam generator. The integration of these systems results in the generation of 5 MW electricity, which is used to run the electrolysis unit. The overall process does not require an extra source of energy, decreasing the external utility requirement. Both the systems have been investigated against various catalysts for the selection of best catalyst, thus enhancing overall process efficiency. The study has been carried out using Aspen HYSYS v 9. Aspen Energy Analyzer v 9 has been used to do the energy analysis of the system. Overall plant costing has been carried out using Aspen Economic Analyzer v 9. Highlights: Integration of MCH dehydrogenation and toluene hydrogenation systems. Modeling and simulation have been carried out using Aspen Hysys v9. 5 MW electricity has been produced as a result of integration. 1 wt% Pt/γ-Al2 O3 found to be best catalyst for both integrated processes. Overall plant costing has been carried out using Aspen Economic Analyzer v9.